LncRNA CDKN2B-AS1 hinders the proliferation and facilitates apoptosis of ox-LDL-induced vascular smooth muscle cells via the ceRNA network of CDKN2B-AS1/miR-126-5p/PTPN7. (1st October 2021) - Li, Jie; Chen, Jia; Zhang, Fan; Li, Jianfeng; An, Shoukuan; Cheng, Ming; Li, Junquan
Abstract: Objective: The patterns of lncRNA CDKN2B-AS1 in coronary heart disease (CHD) have been extensively studied. This study investigated the competing endogenous RNA (ceRNA) network of CDKN2B-AS1 in coronary atherosclerosis (CAS). Methods: Microarray analyses were performed to screen out the CHD-related lncRNAs (CDKN2B-AS1) and the downstream microRNAs (miR-126-5p). The expression of CDKN2B-AS1 in serum of patients with CHD and healthy volunteers was detected. Vascular smooth muscle cells (VSMCs) were treated with oxidized low density lipoprotein (ox-LDL) to establish the cell model. Then pcDNA-CDKN2B-AS1 and/or miR-126-5p mimic were transfected into ox-LDL-treated VSMCs to estimate cell proliferation, apoptosis and inflammation. The ceRNA network of CDKN2B-AS1 along with the possible pathway in CHD was testified. Results: CDKN2B-AS1 expression was low in patients with CHD and ox-LDL-treated VSMCs. Upon CDKN2B-AS1 overexpression, TNF-α, NF-κB and IL-1β levels in VSMCs were decreased, the proliferation of VSMCs was inhibited and the apoptosis rate was increased. Overexpression of miR-126-5p could reverse these trends. CDKN2B-AS1 as a ceRNA competitively bound to miR-126-5p to upregulate PTPN7. CDKN2B-AS1 inhibited VSMC proliferation and accelerated apoptosis by inhibiting the PI3K-Akt pathway. Conclusion: LncRNA CDKN2B-AS1 upregulates PTPN7 by absorbing miR-126-5p and inhibits the PI3K-Akt pathway, thus hindering the proliferation and accelerating apoptosis of VSMCs induced by ox-LDL, thus being a therapeutic approach for CAS. Highlights: CDKN2B-AS1 is downregulated in CHD patients and ox-LDL-induced VSMCs. Overexpression of CDKN2B-AS1 inhibits VSMC proliferation and accelerates apoptosis. CDKN2B-AS1 as ceRNA competitively binds to miR-126-5p to regulate PTPN7. Overexpression of miR-126-5p reverses the effect of pcDNA-CDKN2B-AS1 on VSMCs. CDKN2B-AS1 activates the PI3K-AKT axis to inhibit VSMC proliferation.